2017
DOI: 10.1038/jes.2017.11
|View full text |Cite
|
Sign up to set email alerts
|

Development of a modeling approach to estimate indoor-to-outdoor sulfur ratios and predict indoor PM2.5 and black carbon concentrations for Eastern Massachusetts households

Abstract: The effects of indoor air pollution on human health have drawn increasing attention among the scientific community as individuals spend most of their time indoors. However, indoor air sampling is labor-intensive and costly, which limits the ability to study the adverse health effects related to indoor air pollutants. To overcome this challenge, many researchers have attempted to predict indoor exposures based on outdoor pollutant concentrations, home characteristics, and weather parameters. Typically, these mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…The study in [23] aims to demonstrate the use of machine learning methods in predicting ambient CO 2 . Other research also attempt to develop proxies for estimating BC indoors and outdoors using regression analysis [24], [25] and machine learning methods [12], [26], [27].…”
Section: Introductionmentioning
confidence: 99%
“…The study in [23] aims to demonstrate the use of machine learning methods in predicting ambient CO 2 . Other research also attempt to develop proxies for estimating BC indoors and outdoors using regression analysis [24], [25] and machine learning methods [12], [26], [27].…”
Section: Introductionmentioning
confidence: 99%
“…More thoroughly, I/O concentration ratios calculated for sulfate suggest that during all campaigns an effective penetration of fine particles occurs indoors. This species is, in fact, considered as a good proxy for the estimation of infiltration factor in indoor environments, since it has no indoor sources and is thermally stable over time in both outdoor and indoor environments [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Yuchi and Clark [ 13 , 14 ] used a multiple linear regression (MLR) model to predict indoor home PM 2.5 levels. Tang and his co-workers used the mass balance method to create a prediction model for indoor PM 2.5 levels in homes [ 15 ]. Elbayoumi used an MLR model to estimate indoor PM 2.5 levels in schools [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study observed that outdoor air more critically affects indoor air quality in tropical and subtropical regions than in cold or temperate regions [ 21 ], particularly during cold seasons. Outdoor air is a critical source of PM 2.5 in homes [ 13 , 22 ], and indoor sources, such as cigarettes, cooking, or coal smoke from home heating stoves, are major indoor sources of PM 2.5 [ 13 , 14 , 15 ]. In tropical and subtropical regions, buildings are designed to reduce indoor heat and facilitate air conditioning operations for several hours, whereas in temperate regions, buildings are designed to trap heat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation